Analysis and modeling of the inverted bioconvection in Chlamydomonas reinhardtii: emergence of plumes from the layer of accumulated cells - Naoki Sato; Kaoru Sato; Masakazu Toyoshima (Heliyon, 2018)
Bioconvection is a convective flow found in a suspension of motile cells that swim against gravity, and is a primitive form of order formation of cells, which has been studied both experimentally and theoretically. We formulate here an inverted bioconvection occurring in a suspension of phototactic cells in a high-density medium, which is illuminated from the bottom. We used a highly phototactic strain 137c of Chlamydomonas reinhardtii in the experiments. Using a custom-made lateral microscope, we observed a close view of cellular dynamics in the initiation of inverted bioconvection. In conventional bioconvection, convective flows of cells are formed spontaneously with or without formation of the surface cell layer. In inverted convection, a crowded cell layer was initially formed at the bottom, which was a prerequisite for the subsequent emergence of plumes, namely, floating populations of cells. The plume formation was a result of neither uneven initial cell density nor unequal light intensity. Based on detailed analysis of individual cells, we constructed a model of inverted bioconvection, in which each cell experiences a transition between two modes of movement: phototactically swimming cell and non-motile cell aggregate. A simulation using the CompuCell3D software reproduced basic behaviors of the plume formation. The modal transition has not been a subject of basic studies, but provides an interesting target of study of cell-to-cell interactions.